HARMONI ISLAM DAN BUDAYA LOKAL - Taufik, Muhammad (Jurnal Ilmu Ushuluddin, 2013)
This paper discusses the harmony of Islam and local traditions. This was motivated by Islamic beliefs and interacted with the existing culture and acculturation eventually grew slowly with the local culture was patterned animism, dynamism, and Hindu-Buddhist. Meeting and traditions of Islam in the archipelago reinforced the concept of the harmony of Islam and local culture that could live hand in hand with each value, in example were religious values and the values and traditions that have been acculturated into contact directly. Both were considered by the community something to be respected and preserved. So this proved the fabric of harmony between the two equally spawned Islamic traits that interacted and adapted that spawned a local feature that was commonly referred to as local wisdom.